Monozygotic twins discordant for exstrophy of the urinary bladder. Issue 2 (April 1981) - Bugge, M
Abstract : A pair of monozygotic male twins discordant for ectopia vesicae urinariae is described. There is no reason to think that any exogenic factors contributed to the aetiology. There was no consanguinity and no history of congenital anomalies on either side of the family. Published reports concerning family incidence and twin reports are reviewed.